A new flavone from the Melicope patulinervia (Merr. & Chun) Huang. (1st December 2012) - Liu, Ting; Liao, Haibing; Yuan, Ke; Zhang, Yanbing
A phytochemical study of Melicope patulinervia gave a new flavone 7-(3-methyl-but-2-enyloxy)-5-hydroxy-3, 6, 8-trimethoxy-3′, 4′-methylenedioxyflavone and three known flavones, melibentin, 5-hydroxy-3, 7, 8-trimethoxy-3′, 4′-methylenedioxyflavone, 5-hydroxy-3, 6, 7, 8-tetrameth-oxy-3′, 4′-methylenedioxyflavone. Their structures were elucidated on the basis of spectroscopic analysis combined with chemical methods. The antifungal activities of the isolated compounds were evaluated against four plant pathogenic fungi species.